Big Data for Small Area Estimation: Happiness Index with Twitter Data - Sheerin Dahwan Aziz; Azka Ubaidillah (Politeknik Statistika STIS, 2021)
Data availability for small area level is one of the keys to the success of regional development. However, direct estimation of small areas can produce high error due to inadequate sample sizes so the estimation is not reliable. One of alternative solution to this problem is to use the Small Area Estimation (SAE) method which can improve precision by